Pengaruh Model Pembelajaran Make a Match dan Card Sort terhadap Hasil Belajar Siswa pada Tema 7 Subtema 2 Kelas V SDN 132416 Tanjungbalai T.A 2022/2023 - Dinda Karunia Fitri; Ibrahim Gultom (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the Make A Match and Card Sort Learning Model on student learning outcomes. The implementation of this research involved two classes with a face-to-face learning system where the VA class used the make a match model and the VB class used the card sort model. In this study the research design that will be used is the Nonequivalent Control Group Design. The sample in this quantitative study was class V-A with a total of 24 students as the experimental class I with a total of 10 males and 14 females and Class V-B with a total of 24 students with a total of 10 males and 14 females as experimental class II. The data collection technique in this study was a multiple choice test. The data analysis technique used in this study is the normality test, homogeneity test and the Mann Whitney test. Based on the results of the Wilcoxon test, the value of p = 0.000 was obtained, so it was concluded that there was a significant influence of the card sort model on learning outcomes. On average, the make a match model is better than the card sort model, because the average score (Post Test) on make a match is higher, 16,667, compared to the card sort model, 14,250. Based on the results of the Mann-Whitney test, it was obtained that the value of p = 0.001 <0.05, it was concluded that there was a significant difference in effect between the make a match and card sort models on learning outcomes. In other words, the Make a Match Model is significantly better than the Card Sort Model.